Analysis of F8 mRNA in haemophilia A patients with silent mutations or presumptive splice site mutations. (23rd October 2012) - Zimmermann, M. A.; Gehrig, A.; Oldenburg, J.; Müller, C. R.; Rost, S.
Summary Mutation screenings in haemophilia A (HA) patients identified a great variety of mutations in the factor VIII gene (F8): intron 22 or intron 1 inversions, missense mutations, nonsense mutations, small or large deletions, insertions, duplications and splice site mutations. Mutations which do not result in amino acid substitutions (silent mutations) and intronic variants located outside the splice site consensus sequences cannot be easily classified as causative for HA. In these cases, special prediction software algorithms are applied to estimate their impact on splicing. Here, we present mRNA analysis of novel F8 mutations with possible impact on splicing in four HA patients with silent mutations and seven patients with intronic variants close to or within splice site consensus sequences. Seven of eleven mutations examined in vitro could be shown to have an effect on F8 mRNA splicing and the results were compared to in silico predictions. In addition, to validate the splice site prediction software Alamut v2.0 (Interactive Biosoftware), we compared published F8 mRNA analyses with the results of the in silico prediction. In general, the results of the splice site prediction tools of Alamut were in good accordance with the experimental F8 mRNA analyses, but a fundamental discrepancy between in silico and in vitro analyses was obtained in some cases. In conclusion, this study shows that the functional classification of potential splicing mutations should not only rely on prediction software, but be rather based on mRNA analysis experiments.